New data on the genus Belonogaster de Saussure, with establishment of the atrata species-group (Hymenoptera: Vespidae: Polistinae) - Selis, Marco; Longair, Robert W. (Zootaxa, 2025)
New data on the genus Belonogaster de Saussure, 1854 are provided. The atrata species-group is newly established to include the species with largely unsculpted and bare propodeum, namely Belonogaster atrata von Schulthess, 1912, B. aurata Richards, 1982, B. levior Richards, 1982, and the newly described B. velutina Selis & Longair, sp. nov., with a key to the species and photographic references. The males of Belonogaster aurata, B. maculata Richards, 1982, and B. turbulenta Kohl, 1894 are described for the first time, and new data on distribution and variability are provided for 14 species.